2012
DOI: 10.1007/s10853-012-6599-4
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural and wear behavior of dual reinforced particle (DRP) aluminum alloy composite

Abstract: The present investigations are a comparative study of single and dual reinforcement particles on microstructural features and wear behavior in LM-13 aluminum-silicon alloy. Silicon carbide and zircon sand particles of 20-32 lm are reinforced in the alloy by two-step stir casting method. Wear study reveals that the dual particle reinforcement enhances the wear resistance as compared to single particle reinforcement if mixed in a definite proportion. Study also indicate that a combination of 15 % reinforcement o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…The composites were developed by stir casting route. The detailed description of the casting process is given in our earlier work [2,4]. Dry sliding wear tests of the composites were done by using pin-on-disc method.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The composites were developed by stir casting route. The detailed description of the casting process is given in our earlier work [2,4]. Dry sliding wear tests of the composites were done by using pin-on-disc method.…”
Section: Methodsmentioning
confidence: 99%
“…Aluminum alloy matrix composites (AMCs) are widely used in engineering applications due to high specific strength, high corrosion resistance, ease of fabrication and low cost [1][2][3]. Stir casting is also attractive because of simplicity, flexibility and is most economical for large size components to be fabricated [4]. AMCs with ceramic particles reinforcement are suitable candidate for material used in tribological applications.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16] Apart from these properties, Zr sand particles also possess a very low thermal expansion coefficient in comparison to most of the other ceramic oxides, which are favorable to resist high thermal stresses within Zr particles. In view of the utilization of dual reinforcement particles of SiC and Zr sand, Sharma et al 17 stated that it gives enhanced wear properties as compared to single particle reinforcement, if mixed in a definite proportion.…”
Section: Introductionmentioning
confidence: 99%
“…Sharma et al (2012) have studied the effect of single and dual reinforcement particles on microstructural features and wear behavior in LM-13 aluminum-silicon alloy. They concluded that the dual particle reinforcement enhances the wear resistance as compared to single particle reinforcement.…”
Section: Introductionmentioning
confidence: 99%